Tingkat Pemahaman Lateral dan Inferensial pada Siswa SMA dan Mahasiswa: Studi Komparatif Literasi - Kholiq, Abdul; Nurman, Moh; Septaria, Kiki; Susanto, Moh. Arif; Khoiri, Abdul Aziz (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2025)
This study analyzes the comparison of lateral and inferential reading comprehension levels between high school and college students in Lamongan Regency using a quantitative approach. The participants included 300 high school students and 372 college students. Data were collected through reading comprehension tests and analyzed using the Mann-Whitney test to determine significant differences. The results showed that the average lateral comprehension score was 60.145 for high school students and 63.135 for college students. The Mann-Whitney test yielded a value of 45.693, with a p-value of 0.000, indicating a very significant difference. For inferential comprehension, the average score for college students was 56.99, while for high school students, it was 44.92. The Mann-Whitney test yielded 19,597.5, with a p-value of 0.0000862, confirming a significant difference. These findings suggest that college students have significantly higher lateral and inferential reading comprehension than high school students. This difference may be influenced by educational experience, critical thinking skills, and exposure to complex texts at the college level.